Analisis Kecepatan Angin Di Kota Surabaya Berbantuan Database Online - Bmkg - Putri, Fidia Alhikmah; ., Sudarti; ., Yushardi (Jurnal Pendidikan, Sains Dan Teknologi, 2023)
Surabaya is known as one of the big cities of the Indonesian Government has been literate about the issue of Electricity in the Surabaya area but as the year goes by there will also be many new residents, and the increasing years also need more electricity supply. For this reason, an alternative is needed so that there is a solution to the problem, one of which is the installation of a Savonius type turbine that can work optimally even in areas with low wind speeds. Researchers conducted research in the Surabaya area with the help of the BMKG online database on Nov. 1-Dec. 1, 2023. It was obtained that the minimum wind speed value in Surabaya City was 3 m / s equivalent to 5, 83 knots and the maximum wind speed was 9 m / s or 17, 4 knots. With an average wind speed of 2-4 m / s or the equivalent of 3.8-7.7 knots which is classified through a table of wind speed levels 10 meters above ground the average wind speed of Surabaya City is in class 4 (3.4-5.4 knots).